PROSES EVALUASI PENAWARAN PENGADAAN PEKERJAAN KONSTRUKSI PELELANGAN UMUM SECARA PASCAKUALIFIKASI METODE SATU SAMPUL DAN EVALUASI SISTEM GUGUR - Rusmadi, -; Syahrudin, -; Rafie, - (Jurnal Mahasiswa Teknik Sipil Universitas Tanjungpura, 2016)
Election providers goods and services the government procurement construction work by using the method offer knockout apply the principles efficient, effective, transparent, open, compete, fair / not discriminating and accountable.This research to know evaluation process procurement Construction work on road improvement work layers hotmix roads tapau batubi (1 package) with stages of evaluation document an offer started arimatik of a correction , evalusai administration , technical evaluation and evaluation the price In accordance with perpres number 4 years 2015 (fourth change) perpres number of 54 year 2010 and In the selection of service providers of goods / the government is an evaluation in accordance with the minister public works and public housing Number 31 / PRT / M / 2015 on the third amendment minister for public works regulation number 07 / PRT / M / 2011 about standards and guidelines procurement construction work and services consulting. Keywords: Process, Evaluation, System Autumn.